2023
DOI: 10.1037/rev0000348
|View full text |Cite
|
Sign up to set email alerts
|

From partners to populations: A hierarchical Bayesian account of coordination and convention.

Abstract: Languages are powerful solutions to coordination problems: They provide stable, shared expectations about how the words we say correspond to the beliefs and intentions in our heads. Yet, language use in a variable and nonstationary social environment requires linguistic representations to be flexible: Old words acquire new ad hoc or partner-specific meanings on the fly. In this article, we introduce continual hierarchical adaptation through inference (CHAI), a hierarchical Bayesian theory of coordination and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 237 publications
0
29
0
Order By: Relevance
“…In order for a language to evolve, there needs to be a bias towards informativity and a loss of information (e.g., from a pressure to simplify). Empirical work in experimental semiotics has demonstrated that dyadic coordination provides a bias for informativity [12,19,20] and the shuffling of conversational partners affords information loss [21]; thus, satisfying the criteria for evolution without appealing to acquisition. At the same time, it is generally agreed that language acquisition has a bias for simplicity [11,66,67] resulting in information loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order for a language to evolve, there needs to be a bias towards informativity and a loss of information (e.g., from a pressure to simplify). Empirical work in experimental semiotics has demonstrated that dyadic coordination provides a bias for informativity [12,19,20] and the shuffling of conversational partners affords information loss [21]; thus, satisfying the criteria for evolution without appealing to acquisition. At the same time, it is generally agreed that language acquisition has a bias for simplicity [11,66,67] resulting in information loss.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have argued that that speaker-listener interaction is vital for informative signs to emerge [12,19,20]. Information is lost through shifting conversation partners and generational turn-over, which allows alignment on a generalisable language [21]. Thus, language evolution can occur through dyadic coordination alone [for review of the empirical literature see 6].…”
Section: How Might Languages Evolve Due To Communication?mentioning
confidence: 99%
“…Recently, Hawkins et al . [ 99 ] embedded an RSA model of pragmatic in-the-moment inferences in a model of convention formation and showed how signals with vague meanings can give rise to conventional communication systems. The meaning of a signal can get fixed (e.g.…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…However, if a new user is introduced from the same population, then the central tendency of the random effect is the best initial guess for their intercept. This hierarchical, mixed-effects model (also known as a partial-pooling model) may be understood as a way of interpolating between two extremes which are each prevalent in machine learning (Hawkins et al, 2022). The first extreme, known as a complete-pooling model, ignores group-specific effects and learns a single monolithic model across the pooled dataset.…”
Section: Mixed-effects Modelsmentioning
confidence: 99%